Indi - Khoáng sản đi kèm có triển vọng trong mỏ Chì - Kẽm khu vực chợ Đồn - Dung, Phạm Thị; Anh, Trần Tuấn; Hòa, Trần` Trọng; Phượng, Ngô Thị; Ý, Nguyễn Viết; Ishihara, Shunsho; Cẩn, Phạm Ngọc; Hiếu, Trần Văn (Vietnam Journal of Earth Sciences, 2012)
summary Indium-potential by-product in lead-zinc ore of the Cho Don deposits The Cho Don lead-zinc deposits are situated at the southwest of Cho Don district, about 7 km from the centre. These deposits are sphalerite-galenitepyrite type, occured in middle Paleozoic terrigenous carbonate rocks. They are polymetallic vein type. Ore minerals consist of sphalerite, galenite, pyrite, chalcopyrite, pyrrhotite, arsenopyrite, cassiterite and stannite. The present study reveals the highly potential of In in lead-zinc ores of Cho Don deposits. They have relatively high content of indium in feeding ore (70.6-81.5 g/T), highest in Zn concentrate (522-698 g/T) and in Pb concentrate (23.2-56.2 g/T). Indium concentrates mainly in Fe-rich sphalerite (average 1108.7 g/T). Galenite isn’t significant In carrier, however, they have relatively high content of In in the leadzinc Cho Don deposits. Estimated indium potential resources about 168-193 tones, implying that Indium is a valuable resources of the region.